ROI–Based Tamper Detection And Recovery For Medical Images Using Reversible Watermarking Technique. - M. Al-Qershi, Osamah; Bee, Ee Khoo (2010)

(untitled)
Digital image watermarking is proposed to overcome the problems of security, capacity and cost in health care management systems.